Piagam Madinah Sebagai Fondasi Konstitusi Islam: Telaah Historis dalam Perspektif Sejarah Peradaban Islam - Pusparani, Syahla Aura; Sudjatnika, Tenny (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The Constitution of Medina is a historical document considered the first constitution in Islamic history and a milestone in establishing a multicultural society in Medina. This study aims to examine the Constitution of Medina as the foundational basis of Islamic constitutional thought and its role in shaping a just socio-political and legal system during the Prophet Muhammad's time. Using a historical-qualitative approach, this article explores the background of the Charter’s emergence, its core content, and its impact on the development of early Islamic civilization. The findings indicate that the Charter is not merely a political document but a civilizational foundation that emphasizes justice, unity, interfaith tolerance, and the rule of law. This research highlights the importance of re-examining the intellectual and social legacy of the Constitution of Medina in today’s context.